2021
DOI: 10.21203/rs.3.rs-541471/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Iron Overload in a Cohort of Sri Lankan Patients with Transfusion Dependent Beta Thalassaemia and its Correlation with Pathogenic Variants in HBB, HFE, SLC40A1, and TFR2 Genes

Abstract: Background. Iron overload (IO) is a complication in transfusion dependent beta thalassaemmia (TDT). Pathogenic variants in genes involving iron metabolism may confer increased risk of IO. The objective of this study was to determine the magnitude of the cardiac and hepatic IO and determine whether pathogenic variants in HFE, SLC40A1 and TFR2 genes increase the risk of IO in a cohort of TDT patients in Sri Lanka.Materials and Methods. Fifty-seven (57) patients with TDT were recruited for this study. Serum ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…SLC40A1 (also known as ferroportin) can export iron into interstitial fluid and the general circulation through the basolateral Oxidative Medicine and Cellular Longevity membrane of renal tubular epithelial cells [46]. SLC40A1 downregulation compromises intracellular iron output, causing iron overload and accelerating cellular ferroptosis [47]. In this study, we observed that the HG-or PAinduced decrease in HK-2 cell SLC40A1 levels was reversed following dapagliflozin administration.…”
Section: Discussionmentioning
confidence: 62%
“…SLC40A1 (also known as ferroportin) can export iron into interstitial fluid and the general circulation through the basolateral Oxidative Medicine and Cellular Longevity membrane of renal tubular epithelial cells [46]. SLC40A1 downregulation compromises intracellular iron output, causing iron overload and accelerating cellular ferroptosis [47]. In this study, we observed that the HG-or PAinduced decrease in HK-2 cell SLC40A1 levels was reversed following dapagliflozin administration.…”
Section: Discussionmentioning
confidence: 62%